GM-CSF and ipilimumab therapy in metastatic melanoma: Clinical outcomes and immunologic responses. (2nd April 2016) - Kwek, Serena S.; Kahn, James; Greaney, Samantha K.; Lewis, Jera; Cha, Edward; Zhang, Li; Weber, Robert W.; Leonard, Lonnie; Markovic, Svetomir N.; Fong, Lawrence; Spitler, Lynn E.
ABSTRACT: We conducted a phase II clinical trial of anti-CTLA-4 antibody (ipilimumab) and granulocyte-macrophage colony-stimulating factor (GM-CSF) in 22 patients with metastatic melanoma and determined clinical outcomes and immunologic responses. The treatment consisted of a 3-mo induction with ipilimumab at 10 mg/kg administered every 3 weeks for four doses in combination with GM-CSF at 125 µg/m 2 for 14 d beginning on the day of the ipilimumab infusion and then GM-CSF for 3 mo on the same schedule without ipilimumab. This was followed by maintenance therapy with the combination every 3 mo for up to 2 y or until disease progression or unacceptable toxicity. Blood samples for determination of immune subsets were obtained before treatment, at week 3 (end of cycle 1) and at week 6 (end of cycle 2). Blood samples were also obtained from seven subjects who were cancer-free. The immune response disease control (irDC) rate at 24 weeks was 41% and the overall response rate (ORR) was 32%. The median progression free-survival (PFS) was 3.5 mo and the median overall survival (OS) was 21.1 mo. 41% of the patients experienced Grade 3 to 4 adverse events. We conclude that this combination is safe and the results suggest the combination may be more effective than ipilimumab monotherapy. Further, the results suggest that lower levels of CD4 + effector T cells but higher levels of CD8 + T cells expressing PD-1 at pre-treatment could be a potential biomarker for disease control in patients who receive immunotherapy with ipilimumab and GM-CSF. Further trials of this combination are warranted.